The Interface between competition and data protection law: What Malaysia can learn from the case of facebook - Abdul Rahman, Nasarudin; Zulhuda, Sonny; Setyawati, Ria (Society of Interdisciplinary Business Research, 2025)
This paper aims to explore the interaction between competition and personal data protection law in the light of the Bundeskartellamt’s decision against Facebook for abusing its dominant position through unfair terms relating to personal data processing. Specifically, this paper tries to discuss when breach of data privacy raises competition law concerns. This paper will discuss what Malaysia can learn from the case of Facebook and whether competition law can intervene in the area of data privacy given that competition law applies to all economic sectors and the concept of abuse of dominant position is wide enough to catch various forms of conduct including those that relates to unfair personal data processing. This paper mainly employs a doctrinal legal approach relying on both primary data (such as competition law legislations and cases) and secondary data such as journal articles, competition law guidelines1 Among important findings from this research are: competition law can be used to prevent unfair terms in relation to personal data processing despite the existence of data protection laws. The competition authorities may also refer to data protection principles in establishing an infringement under the competition law due to commonalities of principles in the two legislations, provided that the core element of abusive conduct can be established and there should be close consultation between the two regulators.